Urban accessibility facilitated by apps for PwDs: a systematic literature review (Research, Society and Development, 2022)
This article shows the results of a systematic review of the literature focusing on research on urban accessibility related to application offerings based on integrated platforms that serve various types of People with Disabilities (PwD). Articles related to human-machine interaction that facilitate the accessibility of the PwD and that allow the reduction of material, cognitive and affective barriers to mobility, accessibility and interaction in public environments were analyzed, and these articles were published between the years 2015 and 2022. Altogether 19 articles were mapped and analyzed in order to answer the research questions through validation criteria or potential exclusion. The objective of this research is to contribute to society through social inclusion and applicability of the future solution in smart cities, starting through the experiment on an academic campus. This article also delves into technological and social aspects that can serve as a reference for consultations by researchers, public and private bodies that seek depth in their studies. However, being the topic of great relevance, it is clear that this line of research is still little explored, especially in Brazil, given the limited number of articles available.